THE IMPACT OF INTEGRATED AIS IMPLEMENTATION TO THE PURCHASING AND SALES BUSINESS PROCESSES IN ORDER TO IMPROVE EFFICIENCY AND EFFECTIVENESS: A CASE STUDY OF AN SME IN WEST JAKARTA - Tohang, Valentina; Margaret, Bungan (Bina Nusantara University, 2012)
This exploratory study of the impact of integrated AIS implementation throughout the purchasing and sales business processes in an SME in West Jakarta is aimed to illustrate the result of an implementation of automated AIS in a small business to improve companyâ€™s efficiency and effectiveness.Â The study was conducted through the document review of prior implementation and observation of current business process, and interview. The measurement of efficiency and effectiveness is derived from the accounting basic principles of time and cost efficiency and effectiveness.